REPRESENTASI BEAUTY INCLUSIVITY DALAM KAMPANYE DIGITAL MAKE OVER #BEAUTYALLWAYS: Analisis Semiotika Charles Sanders Peirce - Mawar Kusumadewi (2022)
Make Over #BeautyAllWays digital campaign video brings the concept of musical beauty to the issue of beauty. In line with the values of Make Over, namely professional cosmetics with a complete range of colors, textures, and functions for each product categories. This study aims to find out about the representation of beauty inclusivity from a digital campaign video Make Over #BeautyAllWays which describes a meaningful movement in the world of beauty, namely in displaying the broadest and universal meaning of beauty. This study was analyzed using Charles Sanders Peirce's semiotic approach which examines the triangle meaning semiotics, namely sign (representament), object, and interpretant. The method used in this research is a qualitative method which explains the meaning of the representation of beauty inclusivity behind the video. This study resulted in an analysis of the sign, object, and interpretant of the Make Over #BeautyAllWays digital campaign video. The result of the research conducted is that the Make Over campaign video represents the beauty inclusivity contained in the sign depicted from the professional background of the actors, the objects displayed in the activities of each character in the video shown when they do the 'overcome' stage of difficulties and self-distrust, and interpretant that can be understood through the description of each scene, moving captions, and appropriate background music.